A novel method of frequency regulation in microgrid - Bose,U; Chattopadhyay,SK; Chakraborty,C; Pal,BC (IEEE Transactions on Industry Applications, 2019)
Owing to generation and demand mismatch, thefrequency deviation and the rate of change of frequency (RoCoF)may become drastic at times in an islanded micro-grid. This isdue to increased penetration of non-inertial renewable energysources that brings down the system’s resilience to any kind ofdisturbance. Therefore, efficient control algorithms are requiredto mimic the inertial behavior of a conventional synchronousmachine to arrest/limit any sudden change. This work focuseson frequency regulation of microgrid during transient condi-tions by means of fast-responding external energy reserve. Thecharacteristics of a weak grid has been studied and simulatedthrough modeling a Virtual Synchronous Machine (VSM). Aninverter model is also developed to integrate the Energy StorageSystem (ESS) to the grid and a Double Second-Order GeneralizedIntegrator Phase Locked Loop (DSOGI-PLL) is implementedthat is capable of synchronizing the system under distortedand unbalanced situation. A new technique to estimate thefrequency of the microgrid is reported. A simple proportionalcontroller based approach for different level of pulsed powerinjection (using ultracapacitors and batteries) is proposed andsimulated using MATLAB. Experimental demonstration is madeusing batteries only but with two different current-limits. Thecontroller is implemented using dSPACE1103.